Risk and vulnerability analysis of dryland agriculture under projected climate changes : adaptive response in South African summer rainfall areas - Kephe, Priscilla, Ntuchu (My University, 2020)
Agriculture in South Africa, particularly in the summer rainfall areas, faces the challenge of optimal crop production in the face of climate change. Climate change scenarios for South Africa have been predicted to have a negative impact on agriculture particularly in the summer rainfall areas because of its dependence on climate variables. Within the context of the South African agricultural sector, it has become important to identify who and what is most vulnerable to impacts of climate change, so that support for adaptation can be targeted appropriately. The aim of this study was to assess the hazard of climate change in relation to the production of selected dryland crops, namely: sunflower, soybean, and groundnut in the summer rainfall areas and to model their vulnerability and response to climate change as well as to develop coping and adaptation strategies. A survey of 800 farmers was carried out in three agro-ecological zones of Limpopo and Free State. The population was purposively selected and were present for focus group discussions and questionnaire administration. Questions on agronomic practices, cost of production, climate change impact on productivity, coping and adaptation methods used in the face of climate change were asked. The response showed that farm production was not at the optimum, not only because of the influence of climate but as a result of the poor agronomic practices by the farmers. Following a factor analysis, 70% of the decline in crop yield was attributed to poor farming decisions. A further look at climatic factors affecting farmers indicated that frost with a 0.989 loading was the most climate extreme affecting most of the farmers. In order to buffer the effects of climate change, the farmers undertook various changes in their farm management and also received some support from the various governmental and non-governmental institutions. It was however, found that though there were policies in place for farmer support, such supports were not administered in a timely fashion and some support types were not adequate for the farmers. A correlation between the number of supports received and yields showed an increase in yield for farmers who received more than one type of support and with such variations evident across the agroecological zones. Physical modelling was conducted to model crop suitability based on downscaled data from the Special Report on Emissions Scenarios A2, (SRES A2) for the time periods centred on 2020, 2050 and 2080. The results showed areas which were not suitable for either soybean, sunflower or groundnut production in the future over time with some areas gaining and losing under different farm input regimes. To establish the effects of climate change on yield, a field experiment was carried out for two consecutive seasons and the results obtained were used to feed the AquaCrop crop simulation model to model the effects of climate change on yield under different management conditions.The results obtained from the survey, field experiments and climate indices guided the development of vulnerability indicators in a spatial manner. Using the socioeconomic and biophysical results, the vulnerability of the summer rainfall area was calculated. The results showed that areas in Limpopo, North West, Eastern Cape, and Northern Cape were the most vulnerable. Based on the types of adaptation options employed by farmers which included a change in planting dates, employing support from institutions, other sources of income, farming practices and recommendations for future adaptation, various scenarios were run in a crop simulation model to determine the cropping regimes suitable for the study area. Options included technology, on-farm management, out of farm management, human and social factors. The results indicated that coping and adaptation measures are place specific and the effects of a climate extreme are felt differently by different farming communities and farmers in the same community. It is hence recommended that the government in its policies towards alleviating the risk of farmers to climate change should look at site-specific options and not a one model fits all. Farmers should also play a role in enhancing their adaptive capacity as well. It is only when barriers are bridged and a proper network of communication established alongside resource provision, will there be a change in farmer’s attitude toward implementing suggested adaptation options.
Thesis (Ph.D. (Geography)) -- University of Limpopo, 2020
Keywords: Adaptation; Adaptivecapacity; Climate change; Small holder farmers; Summer rainfall; Risk; Vulnerability; Dry farming; Climate changes; Climatic changes